Faktor yang mempengaruhi ketidakhadiran di kalangan pekerja bukan eksekutif. - Effie Hafizah, binti Abdul Khalik. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This research aims to study the factors affecting the absenteeism of non-execlllive employees in Rajang Port AlIIhority. Research sample of this study involves 50 respondents which cOl/sist of non-executive employees from variollS departments in Rajang Port Allthority. Eight factors have been chosen for this study to determine the relationship between factors affecting the absenteeism. The data collected was analyzed by using the Statistical Package for Social Science version 11.0' (SPSS 11.0). Several statistical methods were used based on their suitability with the hypotheses which is t-Test, One Way ANOVA and Multiple Pearson Correlation. T-test was used to seek the mean different between genders IOwaI'd absellleeism. One Way ANOVA was used to seek the different between tlVO or more variables in this study such as age, marital status and academic stalLls. Meanwhile, Multiple Pearson Correlation wa5 IIsed to seek the relationship between absenteeism and factors relating to work environment, employee relationship with their peers, transportation and health. Overall, based on the result of the hypotheses shows that there are no significant relationship between absenteeism and demographic factor such as gender, age, marital status and academic status, internal factor in organization include work environment and employee relationship with their peers and external factor in organization include transportation and health. This could be due to some other factors that also contribute to absenteeism at Rajang Port Authority.